A Survey of Orthopaedic Conditions in Small Animal Veterinary Practice in Britain - Ness, M. G.; Abercromby, R. H.; May, C.; Turner, B. M.; Carmichael, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
A two-month survey of small animal orthopaedic conditions was conducted by members of British Veterinary Orthopaedic association. Clinicians from 42 clinics participated from a variety of practice including referral, primary care and teaching institutions. A total of 1627 cases were recorded. The case load was dominated by dogs with evidence that in UK cats are underrepresented in veterinary orthopaedic practice. Evidence of breed predisposition to orthopaedic disease in dogs was not detected. The importance of trauma in younger patients and degenerative diseases in older dogs was confirmed. A strong similarity between the case loads seen at primary care and referral practices was recorded. The results of this survey may be useful to those planning clinical orthopaedic teaching and research programmes.Members of BVOA recorded and collated details of all orthopaedic cases seen during February and March 1994. The case load was dominated by dogs with evidence that cats are underrepresented in orthopaedic practice. There were striking similarities between the case loads of primary care and referral institutes. The findings of this survey may help those responsible for planning clinical orthopaedic teaching and research.
Keywords: Survey: Orthopaedic case load